Digitalisasi Dokumen Impor terhadap Efisiensi Waktu oleh PT. Mitra Segara Cargo Semarang - Putri, Wahyuni Ardiana; Utami, Tini; Pambudi, M. Aji Luhur (Politeknik Bumi Akpelni, 2024)
The purpose of this study is, to find out how the effect of using a digitization system in handling import documents on time efficiency at PT. Mitra Segara Cargo Semarang. In this study, the method used is a descriptive qualitative method, with a qualitative approach. The results of this study show that the import document digitization system used at the PT Mitra Segara Cargo Semarang company shows that the use of import document digitization has a role in the efficiency of work time to redeem DO more efficiently 2 hours 9 minutes, EIR Job Order is more efficient 28 minutes, lift off empty payment is more efficient 1 hour 12 minutes, and container repair payment is more efficient 25 minutes. To improve EMKL services, especially for the expenditure of imported goods, competence can be further improved for HR (human resources) in terms of the accuracy of import documents. Furthermore, this research is expected to be able to develop a digitization system in the management of documents in export and import trade, especially for import documents so it is expected that the digitization system can be more efficient in time and faster for the management of import documents carried out by PT. Mitra Segara Cargo Semarang.